Penguatan Self-Confidence Siswa (Studi Kasus Pada Pembelajaran PAI di SMA Darul Ulum Tapen Kudu Jombang) - Suryanti, Suci; Syarif, M.; Saifuddin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Many students still feel uncomfortable when taking Islamic Religious Education (PAI) lessons, especially when asked to express their opinions or speak in front of the class. This condition makes it difficult for teachers to create an active, interesting, and fun learning atmosphere. This study aims to: (1) describe and analyze the teacher's strategy in improving students' self-confidence, and (2) describe and analyze the factors that influence students' self-confidence. This research uses a descriptive qualitative approach, by collecting data from teachers and students in grades X and XI through observation, interviews, and documentation. The results showed that methods such as group work, ice breaking, presentation tasks and support in the form of praise and motivation from teachers have a positive impact on building students' self-confidence. External factors such as encouragement from family, peers, and involvement in P5 activities are also significant supporters. In conclusion, students' self-confidence in PAI learning can be improved by combining interactive learning strategies and a positive learning environment that plays a significant role in developing students' self-confidence in PAI lessons. Keywords: Self-Confidence; Teacher Strategy; PAI Learning.